Pembuatan Personalisasi E-Commerce pada Duta Irama Menggunakan Sistem Rekomendasi dengan Metode Content Based Filtering - Sugiarto, Niko Selamet; Gantini, Tiur (Zenit, 2015)
Duta Irama is a store that specialize in the sale of electronic components. To develop in sale, Duta Irama need a facilities that can manage sales data, products inventory data, and increase the number of customers. Based on the necessary of Duta Irama then will be made an e-commerce websiteapplication in order to fulfill Duta Iramaâs necessary.This website will implement personalization system through the customer. This personalization is expected to attract customer interest, then it can increase number of customers. This personalization can treat customer personally with userecommender system with content based filtering method. This website use PHP as a script programming and MySQL as a database.Keywords: Sales, E-Commerce, Personalization, Content Based Filtering